PILAR-PILAR FILSAFAT ILMU: LANDASAN EPISTEMOLOGI POSITIVISME DAN POSTPOSITIVISME - Heidi, Mutiara; Efendi; Zalnur, Muhammad (As-Sulthan Journal of Education, 2025)
Philosophy emerged as a movement seeking answers rationally and logically, which gradually developed into a field of science. This study aims to comprehensively and systematically examine and explain the pillars of the philosophy of science as the epistemological foundation for the positivism and post-positivism schools of thought. The method used is a literature review, chosen because the author focuses on an in-depth analysis of philosophical and theoretical concepts. The results of this study show that scientific knowledge is supported by three main pillars of the philosophy of science: Ontology, Epistemology, and Axiology. Within the methodological framework, Epistemology plays a central role in determining valid criteria for truth. This led to the emergence of positivism, which was subsequently criticized and modified into post-positivism. The objective is for scientific knowledge to be able to explain and predict phenomena, as well as provide valid benefits.